Urinary incontinence: a problem of the modern woman - Chmielewska, Daria Dominika; Piecha, Magdalena; Kwaśna, Krystyna; Błaszczak, Edward; Taradaj, Jakub; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Inconvenient consequences, reduced quality of life, prevalence of urinary stress incontinence as well as medical and social determinants associated with urinary incontinence are an object of interest for many authors. Urinary incontinence is a social disease due to its high prevalence. Aim of the study: This paper presents the results of a questionnaire among Polish women from the Silesia region aimed to determine declared severity of risk factors and symptoms of urinary incontinence. Material and methods : Women were assigned to one of four comparison groups according to their age. Group A1 involved women aged between 41 and 50, group A2 – 51-60, group A3 – 61-70. Group A4 involved women at the age of 71 and more. Results : Factors related to lifestyle, such as the amount of coffee, smoking and the presence of constipation, occurred in the groups with medium intensity. The prevalence of symptoms of urinary stress incontinence was confirmed by women of all research groups; however, the symptoms were the most prevalent among women aged 71 and more. The intensity of non-modifiable factors occurrence was low. Although group A3 involved more obese women than others, there was no correlation between obesity and severity of symptoms of urinary incontinence in group A3. Conclusions : The results of the analysis of inter-group differences for severity of stress urinary incontinence indicated the highest average scores in the group of the oldest participants, which were significantly higher in comparison to younger groups.